Comparative analysis of adverse drug reaction reports for leukotriene receptor antagonists mainly indicated for allergic rhinitis and asthma: a WHO VigiAccess study - Youlin Dong; Zhigang Xia; Weimin Gao (Frontiers in Medicine, 2026)
Background Leukotriene receptor antagonists (LTRAs), including montelukast, pranlukast, and zafirlukast, are generally well tolerated and widely used for asthma and allergic rhinitis, but they may cause adverse drug reactions (ADRs). We compared their real-world reporting profiles to identify potential agent-specific safety differences. Methods We conducted a descriptive and disproportionality analysis of World Health Organization (WHO) VigiAccess data retrieved on August 1, 2025. Reports were included from each drug's first year available in VigiAccess (zafirlukast, 1997; montelukast, 1998; pranlukast, 2002) through August 1, 2025. Report-level demographics were summarized using the number of individual case safety reports (ICSRs), whereas System Organ Class (SOC)- and Preferred Term (PT)-level percentages used the total number of ADR entries for the corresponding drug as the denominator. Reporting odds ratios (RORs), proportional reporting ratios (PRRs), and 95% confidence intervals (CIs) compared each target LTRA with the other two LTRAs combined. Results We identified 37,621 ICSRs: montelukast, 33,615 (89.4%); pranlukast, 2,109 (5.6%); and zafirlukast, 1,897 (5.0%). Among 96,624 montelukast ADR entries, the SOC Psychiatric disorders accounted for n = 29,498 (30.5%). Positive PT-level signals included nightmares ( n = 1,688, 1.75%; ROR = 45.89, 95% CI: 14.78–142.45; PRR = 45.10, 95% CI: 14.53–139.95), aggression ( n = 1,758, 1.82%; ROR = 28.69, 95% CI: 11.92–69.03; PRR = 28.18, 95% CI: 11.72–67.78), and suicidal ideation ( n = 1,901, 1.97%; ROR = 19.41, 95% CI: 9.69–38.88; PRR = 19.05, 95% CI: 9.52–38.13). Among 2,724 pranlukast ADR entries, Gastrointestinal disorders accounted for n = 809 (29.7%). Zafirlukast showed disproportionate hepatobiliary reporting (ROR = 5.87, 95% CI: 4.88–7.06; PRR = 5.72, 95% CI: 4.78–6.85). Seven neuropsychiatric PTs were shared across all three agents; their counts, ADR-entry proportions, and RORs ranged from 569 to 2,313, 0.59%–2.39%, and 1.22–19.41 for montelukast; 2–99, 0.07%–3.63%, and 0.03–1.82 for pranlukast; and 4–35, 0.08%–0.70%, and 0.06–0.32 for zafirlukast. Conclusions Real-world evidence from spontaneous-report databases suggests differences in the safety-reporting profiles of montelukast, pranlukast, and zafirlukast. However, under-reporting and incomplete clinical information preclude estimation of incidence or causal inference; these findings should be interpreted as safety signals.